(untitled) (VETERINARIA, 2020)
Study presents the production features of the Simmental breed cows determined by milk production in the municipalities of Čačak, Kraljevo and Kragujevac. In these municipalities we followed genetic potencial of the bulls from the veterinarylivestock centers in Velika Plana and Krnjača. Lactation period encompassed 268-392 days, entire lactation milk quantity reached 3,095-4,324 kg, and milkfat 122.25-204.25 kg. Over standard lactation period 2,408-5,222 kg of milk was produced. In standard lactation, correction was made to 4% FCM (fat corrected milk). Duration of the service period of cows was 42-172 days. Duration of the intercalving period was 339-451 days.